Conceptualization of student support by university support staff in an open distance e-learning environment - Pitsoane, Enid Manyaku (Research in Social Sciences and Technology- OpenED Network, 2024)
Student support is seen as a necessity to better students’ progress. For students to succeed when studying at a distance, they need a great deal of support to adjust to the institution of higher learning. Independence theory was used as a lens to understand the role of student support staff in providing services to students. A qualitative case study was employed with a purposive sample of sixteen support staff to explore the role of regional academic coordinators, counsellors, centre managers and librarians, referred to as support staff, in supporting students in an open distance e-learning institution and also to determine their understanding of student support. The results reveal that most of the support staff members were aware of their role in contributing to student success in the institution. They indicated that there is a gap between academics and professional staff where a referral system is lacking to fully support and trace students needing support. Support staff seemed to lack marketing skills to inform and attract students to utilize the services. The results further reveal a lack of technological skills among some of the support staff to facilitate online services for students. The study recommends collaboration among all role players in the institution in order to give holistic support to students and to be trained in technological skills to assist students online.